Modelo De Gestión Basado En El Marketing Mix Para Las Hosterías Del Cantón Morona - Provincia De Morona Santiago - Báez, Luis Alberto Quevedo; Moncayo, Isabel Romané Peñafiel; Vizuete, Danny Daniel Castillo; Erazo, Wiliam Marco Samaniego (European Scientific Journal, ESJ, 2017)
A management model based on marketing mix is a tool that allows the strengthening and development of tourism. Lodging is a service that integrates the value chain of tourism, and the County of Morona in Ecuador seeks to strengthen this service through the five marketing mix components, which are: product, price, distribution, promotion and market. This analysis starts from a situational diagnosis of the components in order to know the current state of the tourism activity. This was taken as a starting point to generate management strategies that contribute to the improvement of the service quality in the touristic sector with an emphasis on generating economic, social, cultural and environmental benefits.